Multiple Impacts of Loss of Plastidic Phosphatidylglycerol Biosynthesis on Photosynthesis during Seedling Growth of Arabidopsis - Kobayashi, Koichi; Endo, Kaichiro; Wada, Hajime (Frontiers in Plant Science, 2016)
Phosphatidylglycerol (PG) is the only major phospholipid in the thylakoid membrane in cyanobacteria and plant chloroplasts. Although PG accounts only for ~10% of total thylakoid lipids, it plays indispensable roles in oxygenic photosynthesis. In contrast to the comprehensive analyses of PG-deprived mutants in cyanobacteria, in vivo roles of PG in photosynthesis during plant growth remain elusive. In this study, we characterized the photosynthesis of an Arabidopsis thaliana T-DNA insertional mutant (pgp1-2), which lacks plastidic PG biosynthesis. In the pgp1-2 mutant, energy transfer from antenna pigments to the photosystem II (PSII) reaction center was severely impaired, which resulted in low photochemical efficiency of PSII. Unlike in the wild type, in pgp1-2, the PSII complexes were susceptible to photodamage by red light irradiation. Manganese ions were mostly dissociated from protein systems in pgp1-2, with oxygen-evolving activity of PSII absent in the mutant thylakoids. The oxygen-evolving complex may be disrupted in pgp1-2, which may accelerate the photodamage to PSII by red light. On the acceptor side of the mutant PSII, decreased electron-accepting capacity was observed along with impaired electron transfer. Although the reaction center of PSI was relatively active in pgp1-2 compared to the severe impairment in PSII, the cyclic electron transport was dysfunctional. Chlorophyll fluorescence analysis at 77K revealed that PG may not be needed for the self-organization of the macromolecular protein network in grana thylakoids but is essential for the assembly of antenna-reaction center complexes. Our data clearly show that thylakoid glycolipids cannot substitute for the role of PG in photosynthesis during plant growth.